How to overcome local policy conflicts that hinder climate actions? A green roof planning dispute between politicization and de‑politicization - Almalla, Rima; Vuolteenaho, Jani; Käyhkö, Jukka (Springer Cham, 2025)
The integration of green infrastructure, such as green roofs (GR), in urban centres is considered crucial for climate change adaptation, and improving environmental quality. Previous research highlights the benefits of GR, including urban heat island mitigation, energy efficiency, biodiversity enhancement, and stormwater management. However, it also addresses the challenges, particularly in cold climates, where seasonal variations affect GR performance. Furthermore, barriers such as policy constraints, financial limitations, and cognitive challenges can hinder the mainstreaming of vegetated roofs. This study examines the political and policy dynamics surrounding GR implementation through a case study of a planning conflict in Turku, Finland. It employs a mixed-method approach, analyzing planning documents, municipal decision-making data, media reports, and stakeholder interviews. Findings reveal that the politicization of GR in Turku was driven by conflicting interests among stakeholders, including a local affordable housing developer. The introduction of the Blue-Green Factor (BGF) planning tool in 2021 facilitated the depoliticization of GR by providing a flexible framework for enhancing urban greenness and stormwater management. This case underscores the importance of adaptive policy frameworks in overcoming local conflicts and advancing urban sustainability goals. The study also contributes to the broader discourse on urban political ecology and critical planning studies, emphasizing the need for context-sensitive approaches to green infrastructure implementation.